Koncepcja wstydu w pismach św. Tomasza z Akwinu oraz wybranych nurtach psychologii współczesnej - Grabowska, Agnieszka (Studia Theologica Varsaviensia, 2017)
This paper examines the concept of shame in the writings of St. Thomas Aquinas, in the context of selected contemporary psychological approaches. The aim of this work is to compare the understanding of shame by selected approaches of modern psychology, with that of St. Thomas, and to show fundamental differences and explain their sources. The source of these differences are atheistic worldview assumptions made by psychologists, who are predominantly evolutionary psychologists and atheistic humanists. Assuming that man is the product of a chance in the process of evolution, they also consistently assume that the environment in which he moves, like himself, is only material and, it is the environment that is the only source of conditioning mechanisms of our behavior. All emotional mechanisms, especially observed consistently across different cultures must have an evolutionary explanation. Shame seems to be for many psychologists pointless and harmful anachronism. St. Thomas, starting from different assumptions, draws different conclusions. Because he assumes the creation of man by absolutely moral Creator of all things, who designed man so that the man could find happiness in Him, the world of values is not only objective, but it is of extreme importance. St. Thomas described the mechanism of shame, as a brake (fear), which is a feeling effecting those, who are subjected to feelings, to prevent them from committing an evil act. For St. Thomas, shame is therefore a purposeful mechanism, which aims to achieve good not only material, but above all spiritual (support the virtue of temperance). Many psychologists today reject the whole concept of St. Thomas, because they do not accept his metaphysics.